Alkaline Earth Guests in Polyoxopalladate Chemistry: From Nanocube to Nanostar via an Open‐Shell Structure1. Issue 44 (12th September 2014) - Yang, Peng; Xiang, Yixian; Lin, Zhengguo; Bassil, Bassem S.; Cao, Jie; Fan, Linyuan; Fan, Yanxuan; Li, Ming‐Xing; Jiménez‐Lozano, Pablo; Carbó, Jorge J.; Poblet, Josep M.; Kortz, Ulrich
Abstract The three novel, discrete palladium(II)‐oxo clusters [CaPd12O8(PhAsO3)8]6− (CaPd12), [SrPd12O6(OH)3(PhAsO3)6(OAc)3]4− (SrPd12), and [BaPd15O10(PhAsO3)10]8− (BaPd15) encapsulating alkaline earth metal ions were prepared and fully characterized by a multitude of solution and solid‐state physicochemical techniques. We have discovered a structure‐directing template effect induced by the respective size of the alkaline earth guest ion, which determines the detailed condensation arrangement of the peripheral PdII‐oxo shell. The unprecedented SrPd12 with an open‐shell type structure is of particular importance and reflects a successful strategy for deliberate design of new structural classes of polyoxo‐noble‐metalates. Furthermore, the unusual acetate–water ligand exchange phenomenon renders SrPd12 as a promising candidate for noble‐metal‐based catalysis.